CONTRASTIVE APPROACH AND TEXTUALITY IN LEGAL TRANSLATION - BIELAWSKI, Paweł (Comparative Legilinguistics, 2018)
This paper focuses on legal translation. First, the author defines legal texts and points to particular responsibility related with legal translation resulting from the status of these texts. Turning to the aspects of translation, the author underlines the boundness of each legal system to the country it is in force. At the same time, he points to the conceptual and terminological uniqueness resulting from this boundness. Against this backdrop, the premisses of, both, the comparative law and comparative terminology are presented. With regard to legal translation the similarities and differences existing between both comparative approaches are stated. In the final step, the author points to the importance of seven standards of textuality in legal translation. The purpose of the present paper is to emphasize the importance of the comparative approach and of the textuality for legal translation. The Author stresses here these aspects of translation which allow the target text to become a functional equivalent to the source text.